Penerapan Culturally Responsive Teaching sebagai Pendekatan untuk Mengoptimalkan Kemampuan Berpikir Kritis Peserta Didik - Khumairotul Khasanah; Ervina Eka Subekti; Ariani Nur Setyaningsih (Journal on Education, 2025)
Critical thinking skills are important skills that must be possessed by 21st century students, but their development at Elementary School level is still constrained by the lack of an approach that accommodates cultural diversity. Culturally Responsive Teaching (CRT) approach offers solution by integrating local cultural values in learning to improve students' critical thinking skills. This study analyzes the application of CRT to optimize students' critical thinking skills. This study uses qualitative method with a descriptive approach, through interviews, observations, and document analysis. The results of the study indicate that the application of the CRT approach can optimize students' critical thinking skills by integrating local culture, increasing active involvement, and creating an inclusive learning atmosphere. Learning models that are integrated with the CRT approach can optimally improve critical thinking skills, including Project Based Learning model, Problem Based Learning model, Discovery Learning model, Cooperative Learning model, and Guide Inquiry model.